Restoring Cocoa to its Throne Policy Recommendations for Revitalizing Trinidad and Tobago's Cocoa I - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The video highlights policies to revitalize the cocoa industry in Trinidad and Tobago, focusing on technology, strategic support and market development to boost the economy, preserve Trinidadian and foster regional integration.